Excitation Equations for Longitudinally-Azimutally Irregular Waveguides Taking into Account the Finite of the Walls Conductivity - А. А. Kurayev; V. V. Matveyenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
Excitation equations for longitudinal-azimuthally irregular waveguides are formulated taking into account losses in the walls. The inner surface of the waveguide walls is given by an arbitrary smooth function b(ϕ, z). The coordinate transformation method replaces the original cylindrical coordinate system r, ϕ, z with a new one ρ, ϕ, z, where ρ = r/(b(ϕ, z)). The new system defines the waveguide boundary as ρ = 1 = const, i. e. the waveguide geometry transforms as a regular cylinder. Taking these functions into account, the standard procedure of the incomplete Galerkin method is used to determine the amplitudes of partial waves. The resulting general equations can be used in the calculation and optimization of both microwave and EHF electronic devices of various types, as well as passive microwave devices of various applications.